Keragaan Fenotipik Klon-Klon Mawar Hasil Persilangan Tunggal - Kurniasih, Dedeh (Universitas Bangka Belitung, 2008)
The information regarding phenotypic performance is very important in rose hybridization and selection program. The aimed of the study was to revael out information on phenotypic performance in order to obtain superior clone from single crossed rose (Rosa hybrida L.). The thirty genotypes were arranged in a randomized complete block design with three replicates and three sub-sampling for individual genotypes. Observations were made on nine quantitative is panjang tangkai, diameter tangkai, neck length, sum of leaf, jumlah duri, diameter kuncup, diameter bunga mekar, jumlah petal, vase life of flower and one qualitative characters is colour of petal. The results of the study showed that phenotypic performance of thirty rose clones had significant difference on all observed characters and the clone number of clone 031-04 showed better performance componed to the others, following by clones number 104-05,026-13,104-03 and 100-31 as proporssing clones. Keywords : rose, phenotypic, performance, clone